Pengaruh Marketing Public Relations terhadap Citra Perusahaan Erigo - Shafwa Gheitsa Zabadiya; Sa’diyah El Adawiyah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Marketing Public Relations is a communication tool that is useful for promoting the advantages of each company's products to increase public trust. Another impact of marketing public relations is creating a positive impression on the public, including towards the Erigo Company. The purpose of this study is to measure the influence of Marketing Public Relations activities on the image of the Erigo company. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed online to 75 respondents. The theories used in this study are the Public Relations theory by Edward R. Bernays and the corporate image theory by Kotler and Keller. The results of the analysis show that Marketing Public Relations has a significant influence on the image of the Erigo company, with a contribution of 65.1% and a correlation coefficient value of 0.812, which is included in the very strong category. It can be concluded that Marketing Public Relations carried out by Erigo effectively supports the formation of the company's image among young consumers.